Additive effect of oral LDD175 to tamsulosin and finasteride in a benign prostate hyperplasia rat model - Choi BR; Kim HK; Soni KK; Karna KK; Lee SW; So I; Park JK (Dove Medical Press, 2018)
Bo Ram Choi,1–3 Hye Kyung Kim,4,* Kiran Kumar Soni,1–3 Keshab Kumar Karna,1–3 Sung Won Lee,5 Insuk So,6 Jong Kwan Park1–3,* 1Department of Urology, Chonbuk National University, Jeonju, Republic of Korea; 2Research Institute of Clinical Medicine of Chonbuk National University-Biomedical Research Institute, Chonbuk National University Hospital, Jeonju, Republic of Korea; 3Clinical Trial Center of Medical Device of Chonbuk National University, Jeonju, Republic of Korea; 4College of Pharmacy, Kyungsung University, Busan, Republic of Korea; 5Department of Urology, Samsung Medical Center, Samsung Biomedical Research Institute, Sungkyunkwan University School of Medicine, Seoul, Republic of Korea; 6Department of Physiology and Biomedical Sciences, Seoul National University College of Medicine, Seoul, Republic of Korea *These authors contributed equally to this work Objective: We investigated the benefits of the BKCa agonist 4-chloro-7-trifluoromethyl-10H-benzo[4,5]furo[3,2-b]indole-1-carboxylic acid (LDD175) combined with tamsulosin and finasteride, in a benign prostatic hyperplasia (BPH) rat model.Materials and methods: Castration was performed by bilateral orchiectomy under ketamine anesthesia. A rat model of BPH was established by daily intramuscular administration of testosterone propionate plus 17β-estradiol for 8 weeks. Model rats were administered combinations of 20 mg/kg LDD175, 0.01 mg/kg tamsulosin and 1 mg/kg finasteride once daily by oral gavage for 4 weeks from week 6 to 9 post-surgery. Intraurethral pressure induced by electrostimulation of the hypogastric nerve was measured at the end of administration. Body and genitourinary organ weights were recorded, serums were assayed for hormone concentrations, and tissues were subjected to histopathology, and analyses of α1-adrenoceptor mRNA and protein expression levels after treatment.Results: Combined LDD175, tamsulosin, and finasteride significantly decreased prostatic index, serum hormone levels, epithelial thickness, and prostate expression of α1-adrenoceptors in BPH model rats. The 3-drug combination was more effective than any other combination or LDD175 alone.Conclusion: These results suggest that LDD175 addition to tamsulosin and finasteride may be beneficial for the treatment of BPH patients who do not respond to tamsulosin plus finasteride. Keywords: α1-adrenoceptors, α1-adrenergic receptor antagonists, benzofuroindole, intraurethral pressure, 5α-reductase inhibitors